2020
DOI: 10.1088/1742-6596/1626/1/012151
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Damage Detection and Recognition Based on Deep Learning

Abstract: Bridge damage detection is of vital importance to bridge safety. Nowadays the damage detection is mainly performed by human which is inefficient. We pro-posed a bridge damage detection and recognition method based on deep learning which is named DT-YOLOv3 in this paper. Our method is based on YOLOv3 object detection method and several improvements were made. First, deformable convolution was used to extract more accurate features, and transfer learning was introduced to improve the detection accuracy. Then, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The experimental results showed that the SPP module could improve mAP by 1.3%; transfer learning could improve mAP by 20.9%. Chen et al 54 used deformable convolution to extract more accurate features based on YOLOV3. Similarly, transfer learning was also used to improve the identification accuracy of rust, collapse, cracks and weeds on the bridge surface.…”
Section: Artificial Intelligence Solutions For Bridge Damage Detectionmentioning
confidence: 99%
“…The experimental results showed that the SPP module could improve mAP by 1.3%; transfer learning could improve mAP by 20.9%. Chen et al 54 used deformable convolution to extract more accurate features based on YOLOV3. Similarly, transfer learning was also used to improve the identification accuracy of rust, collapse, cracks and weeds on the bridge surface.…”
Section: Artificial Intelligence Solutions For Bridge Damage Detectionmentioning
confidence: 99%
“…After testing the model, they evaluated that algorithm can successfully detect cracks in different kind of images. Chen et al (2020) proposed a model for damage detection in concrete bridges using a deep learning model. Their model is based on the technique of transfer learning, taking an existing state-of-the-art object detection algorithm YOLOv3 is used for object localizing.…”
Section: Concrete Structures Condition Assessmentmentioning
confidence: 99%
“…X. Chen et al. (2020) proposed a deep learning method called DT‐YOLOv3 to recognize and detect bridge damage, while Qiao et al. (2021) presented a framework called EMA‐DenseNet that can automatically detect multiple types of damage, including cracks and exposed steel bars on a bridge.…”
Section: Introductionmentioning
confidence: 99%